The Church of the East : a concise history - Baum, Wilhelm, 1948- (Central Asian studies series, 2003)
Currently the only complete history in English of the Syriac Church of the East, this work covers the periods of the Sassanians, Arabs, Mongols, Ottomans and the twentieth century.